2018
DOI: 10.1001/jamapsychiatry.2017.4249
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Exposure-Based Treatment vs Cognitive Processing Therapy for Posttraumatic Stress Disorder: A Randomized Noninferiority Clinical Trial

Abstract: IMPORTANCE Written exposure therapy (WET), a 5-session intervention, has been shown to efficaciously treat posttraumatic stress disorder (PTSD). However, this treatment has not yet been directly compared with a first-line PTSD treatment such as cognitive processing therapy (CPT). OBJECTIVE To determine if WET is noninferior to CPT in patients with PTSD. DESIGN, SETTING, AND PARTICIPANTS In this randomized clinical trial conducted at a Veterans Affairs medical facility between February 28, 2013, and Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
216
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 198 publications
(237 citation statements)
references
References 32 publications
14
216
3
4
Order By: Relevance
“…The demographics of the sample and the study methodology have been described elsewhere (Sloan et al, 2018; Sloan et al, 2016). Briefly, participants were 126 adults (52% male, 54.8% Caucasian) who sought treatment for PTSD.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The demographics of the sample and the study methodology have been described elsewhere (Sloan et al, 2018; Sloan et al, 2016). Briefly, participants were 126 adults (52% male, 54.8% Caucasian) who sought treatment for PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, assessments were conducted at baseline and 6-, 12-, 24-, 36-, and 60-weeks following the first treatment session for both treatment conditions (see Sloan et al, 2016 for additional information); outcomes through the 36-week assessment are reported in Sloan et al (2018). Clinical interviews were administered by masters-level evaluators who were blinded to treatment assignment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations